The Concept of Victorianism in A. S. Byatt’s “Posession” - Костенко, Ганна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2020)
The late 1990s – early 2000s was a time of numerous projects dedicated to the Victorian age and the Victorian novel as a specific phenomenon that inspires the modern novel development. The English postmodern novel with its typical narrative, time transferal to Victorian England, weaving of time layers, invokes current research interest. The relevance of this study is caused by considerable interest of researchers in the Victorian era heritage and by need of a comprehensive study of Victorian linguoculture and its implementation in the modern English novel. The Victorian text influences a new genre of the novel that reflects the gravity of modern English prose to the traditional literature of Victorian era, assumed to be particularly important in this context. The analysis of A. S. Byatt’s “Possession” in the Russian literary criticism was made only by O. A. Tolstykh; in the Ukrainian science, this work was investigated by O. Boynitska in the context of searching the past, so this subject is not investigated enough, and in our opinion is new and relevant, especially from the perspective of the “Victorian era” concept embodied in the novel.The aim of the paper is to analyze the “Victorian era” concept peculiarities in the intercultural context, on the basis of A. S. Byatt’s “Possession” as a Victorian novel. The paper takes into account the reproduction of concepts of Marriage, Home, Family, Freedom, Life, as components of “Victorian era.” The Victorian family is often represented through the place of their dwelling; therefore, the great Victorians’ works are overwhelmed by interior descriptions (Dombey’s house, Miss Havisham’s home, Mr. Rochester’s Castle). However, in “Possession,” there is an obvious contrast of Victorian buildings to the same structures in the XX century: the past prime – the modern decline. All the secrets and delusions hidden behind the facades of supposedly respectable buildings result in distorting facts and, to some extent, to violating the rights of ownership to the memories of the past. This gives another meaning to the title of the novel – “possession,” that is ownership, possession of letters, memory, truth.